The Effect Of Return On Assets, Laverage And Earnings Per Share On Stock Prices With Dividend Policy As Moderating Variables On Property And Real Estate Companies Listed On The Indonesia Stock Exchange For 2016-2019 Period - Sari Manullang, Nova; Pakpahan, Efendy; Br Tarigan, Aremi; Noviyanti Simorangkir, Enda (International Journal of Science, Technology & Management, 2022)
This study aims to examine and analyze the effect of Return On Assets, Laverage, Earning Per Share on Stock Prices with Dividend Policy as moderating variables in property and real estate companies listed on the Indonesia Stock Exchange during the 2016-2019 period. Sample selection was done by using purposive sampling method. The data used is secondary data obtained from the website www.idx.co.id. Data analysis was carried out by calculating the PLS Algorithm using SmartPLS and then testing the hypothesis. The results show that Return On Assets and Earning Per Share have a significant effect on the direction of a positive relationship to Stock Prices, while Laverage has no effect on Stock Prices, and Dividend Policy is able to moderate the effect of Return On Assets on Stock Prices, while Dividend Policy is not able to moderate the influence of Laverage. and Earning Per Share to Share Price.